Comparative genomic expression signatures of signal transduction pathways and targets in paediatric Burkitt lymphoma: a Children's Oncology Group report. (4th May 2017) - Lee, Sanghoon; Day, Nancy S.; Miles, Rodney R.; Perkins, Sherrie L.; Lim, Megan S.; Ayello, Janet; van de Ven, Carmella; Harrison, Lauren; El‐Mallawany, Nader K.; Goldman, Stanton; Cairo, Mitchell S.
Summary: Burkitt lymphoma (BL) is the most common histological subtype of non‐Hodgkin lymphoma (NHL) in children and adolescents. Through the introduction of short intensive multi‐agent chemoimmunotherapy, survival has improved significantly over the past 30 years. However, this successful approach is limited by significant chemotherapy‐induced acute toxicity and risk of developing resistant disease, demonstrating the need to identify less toxic and targeted therapies. We analysed the comparative genomic signature and targetable signalling pathways in paediatric BL (PEBL) samples from the Children's Oncology Group study (ANHL01P1) by genomic profiling and selected genes were confirmed by quantitative real time polymerase chain reaction. These results were compared to PEBL samples from public databases and utilised the Gene Expression Omnibus (GEO) Series (GSE) 10172 and 4475 ( n  = 16), and 4732 ( n  = 15). Three hundred and seventy‐six genes (approximately 25%) were similarly expressed among three PEBL sample groups. Several target genes in Toll‐like receptor signalling, JAK‐STAT signalling and MAPK signalling were significantly overexpressed in PEBL. In addition, several tyrosine kinases, including Bruton tyrosine kinase, protein tyrosine phosphatase and histone deacetylase inhibitor were highly expressed in PEBL. These pre‐clinical results suggest that specific signal transduction pathways are overly expressed in PEBL and several pathways could serve as potential future therapeutic targets.